A Catholic approach to youth depression – implications for those working in Catholic schools, colleges and universities. Issue 2 (3rd July 2019) - Torevell, David
Abstract : Youth depression is a growing phenomenon in schools, college and universities, a major area of pastoral concern which needs addressing, according to many Catholic educators. This article argues that medical/psychiatric approaches and guidance combined with theological and spiritual understandings constitute the most effective way forward. It contends that Catholic educational contexts have a unique opportunity to deal effectively with this matter by highlighting and drawing from the rich heritage of the Church. Its distinctive Christian metaphysics and theological anthropology have much to contribute and can be immensely therapeutic. Such frameworks, however, must only be considered when, in the professional judgement of the teacher/lecturer, it is wise to adopt them. The article concludes by suggesting that the vision of the world offered by Gerald Manley Hopkins (himself a victim of depression) in his poem 'God's Grandeur', is the ultimate goal Catholic educators might wish to strive for.